Italian Validation of the Chiba Interprofessional Competency Scale (CICS29) - Tonarelli, Annalisa; Takeshi Yamamoto, Takeshi; Foà, Chiara; Miraglia Raineri, Alessandra; Artioli, Giovanna; Baccarini, Elena; Giampellegrini, Paola; Masciangelo, Itria; Moggi, Elisa; Toni, Doriana; Valcavi, Luca; Sarli, Leopoldo (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: The Chiba Inter-professional Competency Scale (CICS29) validated in several languages, it is a self-report instrument that investigates the degree of interprofessional collaboration in six areas: attitudes and beliefs of the professional; ability to manage a work group; actions to achieve goals; providing assistance that respects the patient; attitudes and behaviours that improve the cohesion of the working group; fulfilling or performing the own professional role. In addition to being recent, the scale investigates collaboration among all health professionals, and is not limited to specific professionals. The aim of the study was to validate the Italian version of CICS29. Method: A questionnaire-based study was conducted with an Italian sample consisting of 530 health professionals (419 women¸ mean age = 40 years, SD = 10.7; range 23- 58 years). The internal validity was measured using factor analysis. To verify the convergent validity, the Italian Version of Interprofessional Collaborative Competency Attainment Survey (ICCAS) was correlated with the CICS29; Results: The reliability and the internal validity of the CICS29 revealed 6 factors corresponding to the original subscales. The analysis presents an excellent sample adequacy measure (KMO = .933) with the scores ranging from 0.62 to 0.78 for the interclass correlation coefficients of the 6 domains. A significant level of correlation was found between the subscales of the CICS29 and the ICCAS. Conclusions: In conclusion, the Italian version of CICS29 has a satisfactory level of reliability and validity and it is recommended for measuring interprofessional collaboration of the health professionals. (www.actabiomedica.it)